Triphenylene pyrazine-based porous material as well as preparation method and application thereof
Through the high-temperature polymerization reaction of pyrazinyl porous materials of sanoxy pyrazinyl porous materials, the problems of low energy density and insufficient chemical stability of supercapacitor materials are solved, and simple preparation and efficient application of solvent-free and catalyst-free are achieved, with high specific capacitance and long cycle stability sex.
Patent Information
- Application Number
- CN202411107701.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-13
- Publication Date
- 2024-12-27
AI Technical Summary
The low energy density and chemical stability of existing supercapacitor materials are insufficient, and the synthesis process is complicated, making it difficult to achieve large-scale preparation of porous polymer materials without solvents and catalysts.
Using pyrazine-based porous material, high temperature polymerization reaction is carried out in a protective atmosphere by tribromide tripyrazine monomer to form a polymer with high chemical stability and pseudocapacitance activity. It is used in supercapacitors, avoiding solvents and Use of catalyst.
Long cycle stability and high specific capacitance in strong acid or strong alkaline electrolyte are achieved, reducing material synthesis costs, simplifying process steps, and having a wide range of supercapacitor application prospects.
Smart Images

Figure CN119208024A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of capacitor materials, and in particular relates to a tripyrazine-based porous material and a preparation method and application thereof. Background Art
[0002] Nowadays, the advent of the new energy era has also put forward higher requirements for existing energy storage devices. As one of the main energy storage devices at present, supercapacitors have aroused widespread research interest. Compared with batteries, supercapacitors usually have higher power density, faster charge and discharge rate, and longer cycle life, so they are often used in electric vehicles and emergency power supply. However, low energy density greatly limits the further application of supercapacitors. According to the charge storage mechanism, capacitors can be divided into double-layer capacitors and pseudocapacitors. Double-layer capacitors mainly rely on the adsorption and desorption of electrolyte ions on the electrode surface to store energy. Therefore, double-layer capacitors usually have higher power density, but their energy density is low. Pseudocapacitor capacitors store energy through the intercalation of electrolyte ions on the surface of pseudocapacitor materials or the redox reaction on the surface of pseudocapacitor materials, so pseudocapacitor capacitors usually have high energy density and power density. It is well known that high specific capacitance is conducive to achieving high energy density, and the electrochemical performance of capacitors is mainly related to electrode materials. Therefore, designing electrode materials with high pseudocapacitive activity is the key to solving the problem of low energy density of capacitors.
[0003] At present, pseudocapacitive materials mainly include transition metal oxides / hydroxides and conductive polymers. Since metal ions exist in multiple valence states, transition metal oxides / hydroxides can usually undergo multi-step electron transfer reactions, thus being able to exhibit high specific capacitance. However, these inorganic materials have poor designability, making it difficult to meet the requirements of multifunctional material design. Relatively speaking, conductive polymers have better structural designability. However, their dense stacking structure makes it difficult to alleviate the volume changes caused by the electrolyte ion deintercalation during charging and discharging, so conductive polymer materials usually exhibit poor cycle stability. Porous polymers are porous framework materials formed by covalently connecting small organic molecules. They usually have high specific surface area, adjustable pore size, and high structural designability, so they are expected to become ideal pseudocapacitive materials.
[0004] In recent years, studies have reported that porous polymers with pseudocapacitive activity have been used in the field of supercapacitors. However, the chemical stability and pseudocapacitive activity of these materials need to be improved. In addition, the synthesis process of the above materials is usually complicated, and generally requires the use of organic solvents and catalysts, which not only increases the synthesis cost of the materials, but also is not conducive to the continuous large-scale preparation of the materials. Therefore, it is of great significance to design a simple solvent-free and catalyst-free method to prepare porous polymer materials with high pseudocapacitive activity. Summary of the invention
[0005] In order to overcome the problems existing in the above-mentioned prior art, one of the purposes of the present invention is to provide a tripyrazine-based porous material. The second purpose of the present invention is to provide a method for preparing the above tripyrazine-based porous material. The third purpose of the present invention is to provide an application of the above tripyrazine-based porous material.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is:
[0007] The first aspect of the present invention provides a tripyrazine-based porous material, wherein the tripyrazine-based porous material is a polymer containing a tripyrazine structural unit, and its structural formula is shown in formula (I):
[0008]
[0009] Preferably, the specific surface area of the tripyrazine-based porous material is 20 to 200 m 2 ·g -1 .
[0010] The second aspect of the present invention provides a method for preparing the tripyrazine-based porous material according to the first aspect, comprising the following steps:
[0011] Tribromotripyridinium monomer The polymerization reaction is carried out in a protective atmosphere to obtain the tripyrazine-based porous material.
[0012] Preferably, the brominated tripyridine monomer is prepared by a preparation method comprising the following steps: cyclohexanone hexaketone hydrate and 4-bromo-1,2-phenylenediamine are reacted to prepare the tribrominated tripyridine monomer.
[0013] More preferably, the reaction temperature of the reaction is 100-140° C., and the reaction time is 20-28 h.
[0014] More preferably, the mass ratio of the cyclohexanone hydrate to 4-bromo-1,2-phenylenediamine is 1:3.
[0015] More preferably, the reaction is carried out in a protective atmosphere.
[0016] More preferably, the cyclohexanone hydrate and 4-bromo-1,2-phenylenediamine are reacted in glacial acetic acid solvent to obtain the tribromotripyridinium monomer.
[0017] Preferably, the protective atmosphere comprises at least one of nitrogen, helium and argon.
[0018] Preferably, the polymerization reaction is a two-step reaction, specifically: reacting at 380-430° C. for 10-16 hours, and then reacting at 430-470° C. for 3-9 hours.
[0019] More preferably, the polymerization reaction is a two-step temperature increase reaction, and the specific temperature increase procedure is: heating from room temperature to 380-430°C at a rate of 3-7°C / min, and keeping warm for 10-16h; then heating to 430-470°C at a rate of 0.5-2°C / min, and keeping warm for 3-9h.
[0020] Further preferably, the polymerization reaction is a two-step temperature increase reaction, and the specific temperature increase procedure is: from room temperature to 4-6°C·min -1 The temperature was raised to 390-430℃ at a rate of 0.5-2℃·min -1 The temperature is raised to 440-460°C at a rate of 100°C and kept at this temperature for 3-9 hours.
[0021] Preferably, the preparation method further comprises the following steps: after the reaction, washing and drying the product.
[0022] More preferably, the washing is carried out by washing with N,N-dimethylformamide and ethanol in sequence.
[0023] More preferably, the drying is performed under vacuum conditions.
[0024] The third aspect of the present invention provides the use of the tripyrazine-based porous material described in the first aspect in a capacitor.
[0025] Preferably, the capacitor is a supercapacitor.
[0026] More preferably, the capacitor is a pseudocapacitive supercapacitor.
[0027] The beneficial effects of the present invention are:
[0028] (1) The present invention provides a tripyrazine-based porous material, which is a polymer containing a tripyrazine structural unit. The presence of CC bonds in the polymer gives the material high chemical stability. When it is used in a supercapacitor, it can achieve long-cycle stability in a strong acid or strong alkaline electrolyte. In addition, the skeleton of the tripyrazine-based porous material contains a large number of redox active sites. When used in a supercapacitor, a proton-coupled electron transfer reaction can occur under acidic conditions, showing a high specific capacitance. Therefore, the tripyrazine-based porous material of the present invention has high chemical stability and pseudocapacitive activity, and has broad application prospects in the field of supercapacitors.
[0029] (2) The present invention provides a method for preparing a tripyrazine-based porous material, using a tripyrazine monomer (HATN-Br) as a raw material. During a high-temperature thermal polymerization process, the C-Br bond breaks and a CC coupling reaction occurs, thereby polymerizing to form a tripyrazine porous polymer with high chemical stability and pseudocapacitive activity. The polymerization process does not require the use of solvents and catalysts. At the same time, the synthesis cost of the material is low and the synthesis steps are simple, which is conducive to large-scale preparation. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The Fourier transform infrared spectra of PH-1, PH-4 and PH-5 in Example 1 and Comparative Examples 1 and 2 are shown;
[0031] Figure 2 is the PH-1 in Example 1 13 C solid-state NMR spectroscopy;
[0032] Figure 3 This is a scanning electron microscope photo of PH-1 in Example 1;
[0033] Figure 4 is the cyclic voltammetry curve of PH-1 in Example 1;
[0034] Figure 5 is the electrochemical impedance spectrum of PH-1 in Example 1;
[0035] Figure 6 is the constant current charge and discharge curve of PH-1 in Example 1;
[0036] Figure 7 This is the rate performance diagram of PH-1 in Example 1. DETAILED DESCRIPTION
[0037] The present invention is further described in detail below through specific examples. The raw materials used in the following examples, unless otherwise specified, can be obtained from conventional commercial sources or prepared and separated by simple synthesis; the processes used, unless otherwise specified, are conventional processes in the art.
[0038] Example 1
[0039] This embodiment provides a tripyrazine-based porous material, and the specific preparation steps are as follows:
[0040]
[0041] S1. Mix 0.94 g of cyclohexanone octahydrate and 1.69 g of 4-bromo-1,2-phenylenediamine, evacuate with a vacuum pump, and backfill with nitrogen. Add 50 mL of glacial acetic acid, evacuate with a vacuum pump, and backfill with nitrogen, and repeat three times. Reflux at 120 ° C for 24 h under a nitrogen atmosphere. After the reaction is completed, cool to room temperature, vacuum filter, wash with water and ethanol, and vacuum dry to obtain tribromotripyridinium monomer (HATN-Br);
[0042] S2, the tribromotripyridinium monomer (HATN-Br) was placed in a nitrogen atmosphere for high temperature polymerization, first, at 5 ° C min -1 The temperature was raised to 400°C at a rate of 1°C min and maintained for 12 h; then, -1 The temperature was raised to 450°C at a rate of 1.5 °C and maintained for 6 h. After the reaction was completed and cooled, the mixture was washed with N,N-dimethylformamide and ethanol in sequence and dried in vacuo to obtain a tripyrazine porous polymer, which was designated as PH-1.
[0043] Example 2
[0044] This embodiment provides a tripyrazine-based porous material, and the specific synthesis steps are as follows:
[0045] S1. Mix 0.94 g of cyclohexanone octahydrate and 1.69 g of 4-bromo-1,2-phenylenediamine, evacuate with a vacuum pump, and backfill with nitrogen. Add 50 mL of glacial acetic acid, evacuate with a vacuum pump, and backfill with nitrogen, and repeat three times. Reflux at 120 ° C for 24 h under a nitrogen atmosphere. After the reaction is completed, cool to room temperature, vacuum filter, wash with water and ethanol, and vacuum dry to obtain tribromotripyridinium monomer (HATN-Br);
[0046] S2, the tribromotripyridinium monomer (HATN-Br) was placed in a nitrogen atmosphere for high temperature polymerization, first, at 5 ° C min -1 The temperature was raised to 400°C at a rate of 1°C / min and maintained for 12 h. -1 The temperature was raised to 450°C at a rate of 1.50 °C and maintained for 3 hours. After the reaction was completed and cooled, it was washed with N,N-dimethylformamide and ethanol in sequence and dried in vacuo to obtain a tripyrazine polymer, which was recorded as PH-2.
[0047] Example 3
[0048] This embodiment provides a tripyrazine-based porous material, and the specific synthesis steps are as follows:
[0049] S1. Mix 0.94 g of cyclohexanone octahydrate and 1.69 g of 4-bromo-1,2-phenylenediamine, evacuate with a vacuum pump, and backfill with nitrogen. Add 50 mL of glacial acetic acid, evacuate with a vacuum pump, and backfill with nitrogen, and repeat three times. Reflux at 120 ° C for 24 h under a nitrogen atmosphere. After the reaction is completed, cool to room temperature, vacuum filter, wash with water and ethanol, and vacuum dry to obtain tribromotripyridinium monomer (HATN-Br);
[0050] S2. The tribromotripyridinium monomer (HATN-Br) is placed in a nitrogen atmosphere for high temperature polymerization. First, at 5°C min -1 The temperature was raised to 400°C at a rate of 1°C / min and maintained for 12 h. -1 The temperature was raised to 450°C at a rate of 1.50 °C and maintained for 9 hours. After the reaction was completed and cooled, the mixture was washed with N,N-dimethylformamide and ethanol in sequence and dried in vacuo to obtain a tripyrazine polymer, which was designated as PH-3.
[0051] Comparative Example 1
[0052] This comparative example provides a tripyridine polymer, and its specific synthesis steps are as follows:
[0053] S1. Mix 0.94 g of cyclohexanone octahydrate and 1.69 g of 4-bromo-1,2-phenylenediamine, evacuate with a vacuum pump, and backfill with nitrogen. Add 50 mL of glacial acetic acid, evacuate with a vacuum pump, and backfill with nitrogen, and repeat three times. Reflux at 120 ° C for 24 h under a nitrogen atmosphere. After the reaction is completed, cool to room temperature, vacuum filter, wash with water and ethanol, and vacuum dry to obtain tribromotripyridinium monomer (HATN-Br);
[0054] S2. The tribromotripyridinium monomer (HATN-Br) is placed in a nitrogen atmosphere for high temperature polymerization. First, at 5°C min -1 The temperature was raised to 400°C at a rate of 1.50 °C and maintained for 12 hours. After the reaction was completed and cooled, it was washed with N,N-dimethylformamide and ethanol in sequence and dried in vacuo to obtain a tripyrazine polymer, which was recorded as PH-4.
[0055] Comparative Example 2
[0056] This comparative example provides a tripyridine polymer, and its specific synthesis steps are as follows:
[0057] S1. Mix 0.94 g of cyclohexanone octahydrate and 1.69 g of 4-bromo-1,2-phenylenediamine, evacuate with a vacuum pump, and backfill with nitrogen. Add 50 mL of glacial acetic acid, evacuate with a vacuum pump, and backfill with nitrogen, and repeat three times. Reflux at 120 ° C for 24 h under a nitrogen atmosphere. After the reaction is completed, cool to room temperature, vacuum filter, wash with water and ethanol, and vacuum dry to obtain tribromotripyridinium monomer (HATN-Br);
[0058] S2. The tribromotripyridinium monomer (HATN-Br) is placed in a nitrogen atmosphere for high temperature polymerization. First, at 5°C min -1 The temperature was raised to 450°C at a rate of 1.50 °C and maintained for 3 hours. After the reaction was completed and cooled, it was washed with N,N-dimethylformamide and ethanol in sequence and dried in vacuo to obtain a tripyrazine polymer, which was recorded as PH-5.
[0059] Material characterization
[0060] 1. Test methods
[0061] (1) The infrared test steps include: using an infrared spectrometer (Thermo Fisher Nicolet iS50) to measure the Fourier transform infrared spectrum of the potassium bromide tablet sample. Add tripyridylene polymer and an appropriate amount of potassium bromide into a mortar, grind, and tablet. After drying, the Fourier transform infrared spectrum of the sample is tested at room temperature.
[0062] (2) Nuclear magnetic resonance (NMR) spectroscopy was used to determine the NMR spectrum of carbon atoms in tripyridylene polymers.
[0063] (3) The steps of the scanning electron microscope test include: fixing the tripyrazine polymer on a sample stage with conductive glue and drying it in a vacuum oven for 12 hours. After gold spraying, the morphology of the sample is observed at a voltage of 10 kV using a S-4800 cold field emission scanning electron microscope produced by Hitachi High-Tech.
[0064] (4) The nitrogen adsorption-desorption isotherm of the sample was measured using a Quantachrome IQ3 adsorption instrument. The specific steps include: 1. Pretreatment: vacuum degassing the sample at 120°C for 12 h; 2. Testing: The nitrogen adsorption-desorption isotherm of the sample was measured using a Quantachrome IQ3 adsorption instrument. The specific surface area was calculated using the Brunauer–Emmett–Teller (BET) model.
[0065] 2. Test results
[0066] Figure 1 The following are Fourier transform infrared spectra of PH-1, PH-4, PH-5 and HATN-Br. Figure 1 As shown, HATN-Br at 579 cm -1There is a strong stretching vibration absorption peak of the C-Br bond at this location; after high-temperature reaction, the absorption peak of PH-1 at this location becomes weaker, proving the breaking of the C-Br bond during the high-temperature polymerization reaction; the absorption peaks of PH-4 and PH-5 at this location only partially weaken, which shows that the reaction conditions of Comparative Examples 1 and 2 cannot completely break the C-Br bond.
[0067] Figure 2 is the PH-1 in Example 1 13 C solid state NMR spectrum.
[0068] Figure 3 The scanning electron microscope photo of PH-1 prepared in Example 1 is shown in FIG. Figure 3 As shown, PH-1 exhibits a blocky morphology.
[0069] PH-2 and PH-3 were used for the above characterization, and the obtained characterization results were basically consistent with those of PH-1.
[0070] The specific surface areas of PH-1, PH-2 and PH-3 are shown in Table 1:
[0071] Table 1 BET specific surface area of tripyridylene polymer (PH-X)
[0072] Sample name <![CDATA[BET specific surface area (m 2 g -1 )]]> PH-1 44 PH-2 52 PH-3 160
[0073] Experimental testing
[0074] The electrochemical properties of the tripyridinium polymer PH-1 were characterized by a three-electrode system, in which the carbon cloth loaded with PH-1 was used as the working electrode, the graphite rod was used as the counter electrode, the Ag / AgCl electrode was used as the reference electrode, and the 1 mol·L -1 The H2SO4 solution was used as the electrolyte to conduct the electrochemical test. The working electrode was prepared by mixing the active material, the conductive agent carbon black (Ketjen black), and the binder polytetrafluoroethylene (PTFE) slurry in a mass ratio of 7:2:1 evenly and then dripping it on the carbon cloth.
[0075] The three-electrode system was subjected to cyclic voltammetry test, electrochemical impedance spectroscopy test and constant current charge-discharge test on an electrochemical workstation CHI660E (Shanghai Chenhua).
[0076] In order to further illustrate the effect of PH-1 prepared in Example 1, the following characterization was performed.
[0077] Figure 4 The cyclic voltammetry curves of PH-1 prepared in Example 1 at different scanning speeds are shown in FIG. Figure 4 As shown, at 1mV·s -1 At a scan rate of 10 mV·s, PH-1 has an obvious redox peak, proving that PH-1 has pseudocapacitive properties.-1 , PH-1 can still maintain obvious redox peaks, indicating that it has fast charge transfer kinetics.
[0078] Figure 5 The electrochemical impedance spectrum of PH-1 prepared in Example 1 is shown in FIG. Figure 5 As shown, PH-1 has a small interface contact resistance and a smaller diffusion resistance.
[0079] Figure 6 The constant current charge and discharge curves of PH-1 at different current densities are shown in Figure 2. Figure 6 As shown, at 0.5A·g -1 At a current density of 1.5 Å, PH-1 has an obvious charge-discharge platform, corresponding to the redox peak in the CV curve.
[0080] Figure 7 This is the rate performance diagram of PH-1 at different current densities. Figure 7 As shown, PH-1 has a larger specific capacitance: at 1A·g -1 At a current density of 450F·g -1 High specific capacitance.
[0081] The rate performance of PH-2 and PH-3 was further characterized using a three-electrode system. The results are shown in Table 2:
[0082] Table 2 Specific capacitance of tripyridylene polymer (PH-X) at different current densities
[0083]
[0084]
[0085] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A tripyrazine-based porous material, characterized in that: The tripyrazine-based porous material is a polymer containing a tripyrazine structural unit, and its structural formula is shown in formula (I):
2. The method for preparing the tripyrazine-based porous material according to claim 1, characterized in that: The steps include: Tribromotripyridinium monomer The polymerization reaction is carried out in a protective atmosphere to obtain the tripyrazine-based porous material.
3. The method for preparing a tripyrazine-based porous material according to claim 2, characterized in that: The tribromotripyridinium monomer is prepared by a preparation method comprising the following steps: cyclohexanone hydrate and 4-bromo-1,2-phenylenediamine are reacted to prepare the tribromotripyridinium monomer.
4. The method for preparing a tripyrazine-based porous material according to claim 3, characterized in that: The reaction temperature of the reaction is 100-140° C., and the reaction time is 20-28 hours.
5. The method for preparing a tripyrazine-based porous material according to claim 2, characterized in that: The protective atmosphere comprises at least one of nitrogen, helium and argon.
6. The method for preparing a tripyrazine-based porous material according to claim 2, characterized in that: The polymerization reaction is a two-step reaction, specifically: reacting at 380-430° C. for 10-16 hours, and then reacting at 430-470° C. for 3-9 hours.
7. The method for preparing a tripyrazine-based porous material according to claim 6, characterized in that: The polymerization reaction is a two-step temperature increase reaction, and the specific temperature increase procedure is: from room temperature to 3-7°C·min -1 The temperature was raised to 380-430℃ at a rate of 0.5-2℃·min -1 The temperature is raised to 430-470°C at a rate of 100°C and kept at this temperature for 3-9 hours.
8. Use of the tripyrazine-based porous material according to claim 1 in capacitors.
9. The use according to claim 8, characterized in that: The capacitor is a supercapacitor.
10. The use according to claim 9, characterized in that: The capacitor is a pseudocapacitor supercapacitor.
